Suitability of peracetic acid for sterilization of media for mycoplasma cultures. - Wutzler, P (1975)
The utility of peracetic acid for sterilization of serum and yeast extract additions to mycoplasma medium was studied by culturing six Mycoplasma species. Culture media containing additions that had been sterilized with peracetic acid proved to be as good as filtered components. The use of 0.05 to 0.1% peracetic acid is recommended to sterilize the serum and yeast extract additions since savings in time and equipment can be accomplished.